(3GdLOhi GdEbJUGOjI ddeTQhYGJ (B/s ((3YeGf(B: s (3OGQ GdMGeO ddfTQ(B, s, 2002)
(3GdEWGQ GdYGeI dOQGSI GdLOhi GdEbJUGOjI ddeTGQjY, GNJjGQ GdeTQhY GdEbJUGOj, YGed GdhbJ hCKQg aj OQGSI LOhi GdeTQhYGJ, GdeYGjjQ GdQFjSjI dJbjje GdeTQhYGJ, GdJMOjGJ GdJj JhGLg YedjI Jbjje GdeTQhYGJ, MGdGJ JWHjbjI TGedIs
Keywords: (3GSJKeGQs; (3GdEbJUGOs